2023
DOI: 10.3390/nano13172482
|View full text |Cite
|
Sign up to set email alerts
|

High-Linearity Wireless Passive Temperature Sensor Based on Metamaterial Structure with Rotation-Insensitive Distance-Based Warning Ability

Chenying Wang,
Luntao Chen,
Bian Tian
et al.

Abstract: A wireless passive temperature sensor based on a metamaterial structure is proposed that is capable of measuring the temperature of moving parts. The sensor structure consists of an alumina ceramic substrate with a square metal double split-ring resonator fixed centrally on the ceramic substrate. Since the dielectric constant of the alumina ceramic substrate is temperature sensitive, the resonant frequency of the sensor is altered due to changes in temperature. A wireless antenna is used to detect the change i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Second, the initial resonant frequency is different at each distance. It is not a large change, but it is observable and was seen by other researchers completing near-field passive sensor testing [ 14 , 15 , 16 ]. Ma et al showed that as the distance increased, the initial frequency peak tended to shift to a higher frequency with a lower peak intensity and there was a larger shift with higher conductivity.…”
Section: Resultsmentioning
confidence: 86%
“…Second, the initial resonant frequency is different at each distance. It is not a large change, but it is observable and was seen by other researchers completing near-field passive sensor testing [ 14 , 15 , 16 ]. Ma et al showed that as the distance increased, the initial frequency peak tended to shift to a higher frequency with a lower peak intensity and there was a larger shift with higher conductivity.…”
Section: Resultsmentioning
confidence: 86%